Product liability entering the twenty-first century : the U.S. perspective - Moore, Michael J., 1953- (AEI-Brookings Joint Center for Regulatory Studies, 2001)
Are liability "crises" an inevitable part of the modern industrial landscape' Does the inherent nature of the insurance industry promote recurring liability crises' What have been the effects of the liability reforms of the 1990s' Should lawyers be given de facto regulatory authority' This report provides perspective on these and other key issues concerning the law and economics of products liability. The authors begins with a brief description of the evolution of products liability doctrine in the U.S., up to the point of the liability crisis of the late 1980s. They discuss the economic implications of product risk for both consumers and producers, offer economic hypothesis on the implications of the increased scope of liability and subsequent reforms, and provide an update of trends in litigation and liability law. The book ends with a discussion of pending legislation and prospects for further improvements. Moore and Viscusi make the point that effective liability policy calls for a balancing of the incentives for improved public safety on one hand, and the benefits of new and existing products on the other.